Emerging and Disruptive Next-Generation Technologies for POC: Sensors, Chemistry and Microfluidics for Diagnostics - Chiriacò, Maria Serena; Ferrara, Francesco; Primiceri, Elisabetta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Recently, the attention paid to self-care tests and the easy and large screening of a high number of people has dramatically increased. Indeed, easy and affordable tools for the safe management of biological fluids together with self-diagnosis have emerged as compulsory requirements in this time of the COVID-19 pandemic, to lighten the pressure on public healthcare institutions and thus limiting the diffusion of infections. Obviously, other kinds of pathologies (cancer or other degenerative diseases) also continue to require attention, with progressively earlier and more widespread diagnoses. The contribution to the development of this research field comes from the areas of innovative plastic and 3D microfluidics, smart chemistry and the integration of miniaturized sensors, going in the direction of improving the performances of in vitro diagnostic (IVD) devices. In our Special Issue, we include papers describing easy strategies to identify diseases at the point-of-care and near-the-bed levels, but also dealing with innovative biomarkers, sample treatments, and chemistry processes which, in perspective, represent promising tools to be applied in the field.